LAMINATED OBJECT MANUFACTURING-LOM - Florin CIOFU; Alin NIOAŢĂ (Fiabilitate şi Durabilitate)
The fabrication of stratified pieces (LOM) is a fabrication method where a 3D model is constructed by adding, pasting and cutting the sections in a cycle that repeated starting with the first layer at the bottom of the piece and ending by the last layer at the top of the piece.